SO020NEPHROLOGY INTERVENTION IN PATIENTS AWAITING CARDIAC SURGERY: A RANDOMISED CONTROLLED TRIAL. (6th June 2020) - Codina, Sergi; Coloma, Ana; Sbraga, Fabrizio; Boza, Enric; Vazquez-Reveron, Jose Maria; Ferreiro, Eva; Cruzado, Josep; Montero, Nuria
Abstract: Background and Aims: Acute kidney injury (AKI) is a frequent complication after cardiac surgery. Its incidence ranges from 19 to 44% depending on the study and which definition is used. There are some well‐known risk factors associated with AKI, including baseline patient characteristics (age and comorbidities), need of perioperative blood transfusion or presence of previous chronic kidney disease. We wanted to evaluate if a nephrologist management and control of potential risk factors of renal disease can be used to prevent AKI, thereby minimizing the risk of need RRT, reducing costs and improving survival in these patients. It will be the first study focused on this intervention. The aim of this study is to assess if a nephrology intervention before cardiac surgery can reduce the postoperative incidence of AKI. Method: Unicentric prospective randomized controlled trial of 298 participants from 2015 to 2019. The inclusion criteria was patients undergoing scheduled cardiac surgery of > 18 years old. The exclusion criteria was a requirement for renal replacement therapy before surgery. Clinical Research Ethics Committee of Bellvitge has approved the study before initiation. All patients have given written informed consent. We have done an intention-to-treat analysis, continuous variables have been compared between groups using Student's t test and categorical variables using X 2 . Results: Nephrology intervention before surgery, included a preoperative study done minimum 1 month before the surgery to optimize the patient' s overall condition by optimization of hydration state, remove or minimize dose of drugs that potentially deteriorate kidney function and correct metabolic disorders. No differences in the characteristics of the patients between groups was found (Table 1). The number of patients with AKI were 49 without differences between groups (0.112), with most of them presenting a stage 1 AKI, only 3 patients present a stage 3 AKI, but none of them required renal replacement therapy (Table 2). We found 1.3% of mortality (1 participant in the intervention group and 3 in control group). Data at 1 year follow-up (n= 144) showed low incidence of kidney disease (creatinine in intervention arm 91.87±30.79μmol/L and in control arm 87.08±23.58, p=0.292) without differences in albuminuria. Conclusion: In summary, we did not find any difference in acute kidney injury and death when a nephrology intervention is done to cardiac surgery patients, probably it would be necessary to increase the sample size to make conclusions. The results at 1 year follow-up showed no kidney disease in these patients.